THE IMPACT OF USING TAX INFORMATION SYSTEMS ON IMPROVING TAX REVENUES / (FIELD STUDY AT THE GENERAL TAX AUTHORITY) - M. Alaa Yahya Younis Saeed (Scholars Digest Publishing, 2024)
This research aims to study tax information systems, which calls for the need for an effective system that meets the needs of the tax administration in terms of data and information and is built on sound and scientific foundations and its role in enhancing tax revenues, and to know the effectiveness of the information systems used by the tax authority to detect taxpayers’ violations of trying to hide their data and the sources of their subject income. For taxation, the first section dealt with the methodology in terms of its importance, problem, hypothesis, and objectives of the research, and the first section also dealt with previous studies, The second section dealt with the theoretical aspect, a theoretical introduction to tax information systems and tax revenues, while the third section dealt with the practical aspect, and the fourth section was the most important conclusions and recommendations, and we mention the most important recommendations are It is necessary to develop a tax reform program that works to develop tax information systems that contribute to developing all aspects of the tax system, which has an important role in the process of counting taxpayers’ incomes and the method of calculating taxes on them.
Keywords: tax information systems, tax revenues